Prevalencia de ansiedad y depresión en pacientes de consultorios externos del policlínico Juan José Rodríguez Lazo - EsSalud - Luyo Gonzales, Moises (Universidad Nacional Federico Villarreal, 2006)
Prevalencia de ansiedad y depresión en pacientes de consultorios externos del policlínico Juan José Rodríguez Lazo - EsSalud
Keywords: Prevalencia; Ansiedad; Depresión; Pacientes; Consultorios; Externos; Policlínico; Juan; José; Rodríguez; Lazo; Essalud; https://purl.org/pe-repo/ocde/ford#5.01.00